Enhancing Collaboration and Science Learning Outcomes Using the Team Games Tournament Cooperative Learning Model Assisted by Wordwall Media among Seventh-Grade Students of SMPN 8 Magelang - Fa'idun Ni'am; Rina Rahayu (Jurnal Penelitian Pendidikan IPA, 2026)
Collaboration skills as one of the 4C skills emphasized in the 21st-century learning concept are crucial for students to interact positively, work in teams, take responsibility in completing task, and improves learning outcomes. This classroom action research conducted in two cycles, aimed to improve collaboration skills and science learning outcomes by applying the Team Games Tournament (TGT) cooperative learning model assisted by Wordwall media. The subjects of this study were 31 students from class VII A at SMPN 8 Magelang. The instruments used were a collaboration skills observation sheet and a pretest-posttest sheet. The data obtained were then analyzed using a descriptive quantitative method with score analysis, skill assessment criteria, and test analysis with N-Gain. The results showed that applying the TGT cooperative learning model with Wordwall improved students' collaboration skills across all aspects, including active contribution, productive work, responsibility, and mutual respect, with most aspects improving from the ‘collaborative’ to ‘highly collaborative’ criterion. Students’ learning outcomes also improved, as shown by the increase in N-Gain scores from Cycle I to Cycle II for indicators C2 (from 0.75 to 0.76), C3 (from 0.72 to 0.74), and C4 (from 0.75 to 0.81).